PERSEPSI MASYARAKAT TERHADAP KEBERADAAN PETERNAKAN BABI DI DESA TOMBI KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Rahayu, Ritha; Maksum, Haerani; Syukur, Suharno H.; Raidhan, Taufiq Eka; Rangi, Jefri Kristianto (SINERGI : Jurnal Riset Ilmiah, 2024)
Raising pigs is one of the businesses managed by a portion of the population in Indonesia. This is because it can provide great benefits if managed properly, including the manure which can be used as fertilizer and a promising source of feed ingredients. This study aims to determine Community Perceptions of the Existence of Pig Farms in Tombi Village, Ampibabo District, Parigi Moutong Regency. This research took place in Hamlet I and Hamlet II, Tombi Village, Ampibabo District, Parigi Moutong Regency. It was carried out from September to November 2022. The type of research used was descriptive qualitative. The method used is survey method (observation and interview). The population in this study were all the people in hamlet I and hamlet II of Tombi Village, totaling 229 people. Determination of the number of samples using descriptive statistics based on the Slovin formula as many as 70 people and the method of taking respondents using accidental sampling. Data analysis used in this study is descriptive statistics using a Likert scale. The results of this study revealed that the public's perception of the existence of a pig farm in Tombi Village, Ampibabo District, Parigi Moutong Regency, as a whole was disturbed. snoring, continuous noise and loud noises with a weight of 43.3%, waste treatment with indicators piled up in the disposal pond and lack of cleanliness with a weight of 77.25% and socio-culture with indicators of community approval and adaptation to smells and sounds with an index value of 60.63% The data shows that respondents feel disturbed by the existence of pig farms close to residential areas, even though it is known that setting up pig farms must be far from residential areas, so as not to disturb the comfort of the people who live in Hamlets I and II of Tombi Village.